Cluster based Oat-vetch mixtures for forage production in Dodola district of West Arsi Zone, Ethiopia - Nabi Husein; Lelisa Diriba (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The present activity was conducted at Keta Berenda kebele of Dodola district of West Arsi Zone of Oromia in 2019 cropping season with the objectives to evaluate cluster-based pre-scaling up fodder oat mixture with vetch, collect farmers' opinion on the performance of the technology, improve farmers' knowledge and skill of application of the improved technology through training and increase local capacity for future scaling-up. Keta Berenda kebele was purposively selected from the district based on the livestock population potential and accessibility. Thirty-one farmers (24 males and 7 females) who had the willingness to accept and disseminate the technology and possess adequate land for forage production were selected in cluster form and established as 1 FREGs in collaboration with development agents of the Kebele. Fourteen trial farmers were nominated from the members for forage establishment. The technology was established on a land size of 2.945 ha with all recommended agronomic practices. The training was given for 20 farmers and 3 development agents on; forage production, management, and utilization practices. 8.01 t ha-1 biomass yields were obtained from an oat-vetch mixture. Hence, the technology should be further promoted on a wide scale to address the feed shortage scarcity of the study area.